2018
DOI: 10.1063/1.5016976
|View full text |Cite
|
Sign up to set email alerts
|

Electron heating in the laser and static electric and magnetic fields

Abstract: A 2D slab approximation of the interactions of electrons with intense linearly polarized laser radiation and static electric and magnetic fields is widely used for both numerical simulations and simplified semi-analytical models. It is shown that in this case, electron dynamics can be conveniently described in the framework of the 3/2 dimensional Hamiltonian approach. The electron acceleration beyond a standard ponderomotive scaling, caused by the synergistic effects of the laser and static electro-magnetic fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…34-36 and the references therein). The numerical simulations 40,41 demonstrated that in the presence of quasi-static electromagnetic fields, an onset of stochasticity is accounted for the electron heating which is depressed by the superluminal phase velocity. However, the mechanism of the stochastic heating is still not clear.…”
Section: Introductionmentioning
confidence: 97%
“…34-36 and the references therein). The numerical simulations 40,41 demonstrated that in the presence of quasi-static electromagnetic fields, an onset of stochasticity is accounted for the electron heating which is depressed by the superluminal phase velocity. However, the mechanism of the stochastic heating is still not clear.…”
Section: Introductionmentioning
confidence: 97%
“…In this letter, we will examine the electron dynamics in multiple laser waves by employing the Hamiltonian approach with the proper choices of canonical variables and time, such that the Hamiltonian is time independent in zero-order approximation [12]. Following [6][7][8][9], we will be focused on the case where one of the laser waves is much stronger than others, which could be considered as a perturbation.…”
mentioning
confidence: 99%
“…Introducing the variable y y y p P A  , after some algebra similar to that in [18], the 3/2D Hamiltonian equations read y dp H dy    , and y dy H dp…”
Section: /2d Hamiltonian and Electron Trajectoriesmentioning
confidence: 99%
“…However, due to the multidimensionality of the system and the strong nonlinearity of the relativistic electron dynamics, the fully theoretical analysis of electron dynamics in the synergistic quasi-static and laser fields is still an interesting problem. Recently, it was shown that the electron dynamics in an arbitrarily polarized laser radiation and transverse or longitudinal quasi-static electric fields as well as transverse magnetic field can be described by the 3/2 dimensional (3/2D) Hamiltonian approach [17,18], which greatly simplifies the analysis of electron interactions with laser and quasi-static electromagnetic fields. It was demonstrated [19] that, the acceleration of electron is attributed to an onset of stochasticity [20,21].…”
Section: Introductionmentioning
confidence: 99%